Glacier clear ice bands indicate englacial channel microbial distribution. Issue 265 (22nd October 2021) - Varliero, Gilda; Holland, Alexandra; Barker, Gary L. A.; Yallop, Marian L.; Fountain, Andrew G.; Anesio, Alexandre M.
Abstract: Distant glacial areas are interconnected by a complex system of fractures and water channels which run in the glacier interior and characterize the englacial realm. Water can slowly freeze in these channels where the slow freezing excludes air bubbles giving the ice a clear aspect. This ice is uplifted to the surface ablation zone by glacial movements and can therefore be observed in the form of clear surface ice bands. We employed an indirect method to sample englacial water by coring these ice bands. We were able, for the first time, to compare microbial communities sampled from clear (i.e. frozen englacial water bands) and cloudy ice (i.e. meteoric ice) through 16S rRNA gene sequencing. Although microbial communities were primarily shaped and structured by their spatial distribution on the glacier, ice type was a clear secondary factor. One area of the glacier, in particular, presented significant microbial community clear/cloudy ice differences. Although the clear ice and supraglacial communities showed typical cold-adapted glacial communities, the cloudy ice had a less defined glacial community and ubiquitous environmental organisms. These results highlight the role of englacial channels in the microbial dispersion within the glacier and, possibly, in the shaping of glacial microbial communities.